2012
DOI: 10.1007/s12031-012-9839-9
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Application of Secretin, Similarly to Intracerebroventricular Administration, Influences the Motor Behavior of Mice Probably Through Specific Receptors

Abstract: Secretin and its receptors show wide distribution in the central nervous system. It was demonstrated previously that intravenous (i.v.) and intracerebroventricular (i.c.v.) application of secretin influenced the behavior of rat, mouse, and human. In our previous experiment, we used a special animal model, Japanese waltzing mice (JWM). These animals run around without stopping (the ambulation distance is very limited) and they do not bother with their environment. The i.c.v. secretin attenuated this hyperactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our PurSct À / À mice had similar learning deficits, suggesting a role for cerebellar SCT in motor learning. Moreover, ICV injection or intranasal application of SCT attenuated repetitive circular movements and improved horizontal activities in Japanese waltzing mice (Heinzlmann et al, 2012;Koves et al, 2011). This study illustrated the role of SCT in restoring normal behavioral patterns, which is also supported by our studies in which SCT knockout led to impaired motor regulation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our PurSct À / À mice had similar learning deficits, suggesting a role for cerebellar SCT in motor learning. Moreover, ICV injection or intranasal application of SCT attenuated repetitive circular movements and improved horizontal activities in Japanese waltzing mice (Heinzlmann et al, 2012;Koves et al, 2011). This study illustrated the role of SCT in restoring normal behavioral patterns, which is also supported by our studies in which SCT knockout led to impaired motor regulation.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study using SCTR knockout mice demonstrated hyperactivity and impaired rotarod performance (Nishijima et al, 2006). Other studies showed that stereotypic circular movements in Japanese waltzing mice were attenuated by central injection or intranasal application of SCT, which increased the horizontal movement and ambulation distance but did not influence the exploratory behavior (Heinzlmann et al, 2012;Koves et al, 2011). However, a comprehensive study focusing on fine motor control and motor learning functions of SCT has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…ASD is a neurodevelopmental disorder characterized by impairments of social and learning skills and repetitive behavior. Interestingly, SCT or SCTR deficiency results in autistic-like traits, including impaired social recognition (Nishijima et al, 2006 ; Takayanagi et al, 2017 ) and motor learning (Jukkola et al, 2011 ; Williams et al, 2012 ; Zhang et al, 2014 ), while SCT treatment attenuates autistic-like behaviors such as repetitive movements and hyperactivity (Köves et al, 2011 ; Heinzlmann et al, 2012 ). Furthermore, some of the cerebellar deficits in Sct−/− mice are in line with previous studies on both ASD patients and rodent models, which reported decreased cerebellar PC number (Fatemi et al, 2012 ; Skefos et al, 2014 ), impaired PC dendritic formation (Peter et al, 2016 ), and GC apoptosis (Yochum et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the CNS, SCT may reach its target sites by axonal transport. The multiple routes of SCT in affecting central functions are supported by the observation that either of ICV, IV, IP, or even intranasal administration of SCT (48) could induce behavioral changes.…”
Section: Future Perspectives: the Full Paradigm Of Sct In Neurobehavimentioning
confidence: 98%
“…In SCTR KO mice, lower open-field activity and deficits of motor learning on rotarod were reported (9). Other groups showed that stereotypic circular movements in Japanese waltzing mice were attenuated by ICV or intranasal application of SCT, which improved horizontal movements but did not influence the explorative behavior (47, 48). One recent study suggested SCT in enhancing eye-blink conditioning, a classical cerebellar-related learning behavior (49).…”
Section: Sct Regulates Motor Coordination and Motor Learning Behaviormentioning
confidence: 99%